Digitizing Flood Processes for Sarawak River Operations - Mah, Darrien Yau Seng; Putuhena, Frederik Josep (Construction Research Institute of Malaysia (CREAM), 2020)
Kuching city of the Sarawak State, Malaysia is located on a flat alluvial plain 30 km away from the sea. In 1998, a barrage was established near estuary to protect the city. This paper reports a computer modelling efforts to guide the barrage operations in flood warning. We present a way of warning based on computerized flood mappings. The behaviours of the river in terms of levels, rates of flow, and other parameters are simulated. The riverside communities are to be alerted at lower river water levels between 0.8 and 1.0 m MSL as compared to the currently used 1.37 m MSL for flood warning with reference to Batu Kawa.